A locus for an auditory processing deficit and language impairment in an extended pedigree maps to 12p13.31-q14.3. - Addis, L; Friederici, A; Kotz, SA; Sabisch, B; Barry, J; Richter, N; Ludwig, A; Rübsamen, R; Albert, F; Pääbo, S; Newbury, D; Monaco, A (2010)
Despite the apparent robustness of language learning in humans, a large number of children still fail to develop appropriate language skills despite adequate means and opportunity. Most cases of language impairment have a complex etiology, with genetic and environmental influences. In contrast, we describe a three-generation German family who present with an apparently simple segregation of language impairment. Investigations of the family indicate auditory processing difficulties as a core deficit. Affected members performed poorly on a nonword repetition task and present with communication impairments. The brain activation pattern for syllable duration as measured by event-related brain potentials showed clear differences between affected family members and controls, with only affected members displaying a late discrimination negativity. In conjunction with psychoacoustic data showing deficiencies in auditory duration discrimination, the present results indicate increased processing demands in discriminating syllables of different duration. This, we argue, forms the cognitive basis of the observed language impairment in this family. Genome-wide linkage analysis showed a haplotype in the central region of chromosome 12 which reaches the maximum possible logarithm of odds ratio (LOD) score and fully co-segregates with the language impairment, consistent with an autosomal dominant, fully penetrant mode of inheritance. Whole genome analysis yielded no novel inherited copy number variants strengthening the case for a simple inheritance pattern. Several genes in this region of chromosome 12 which are potentially implicated in language impairment did not contain polymorphisms likely to be the causative mutation, which is as yet unknown.